Pengaruh Religiusitas, Pengetahuan dan Kesadaran Halal Terhadap Minat Beli Sunscreen Azarine Pada Gen-Z di Surabaya - Anwar, Lukman Hakim; Anwar, Moch khoirul (Jurnal Ekonomika dan Bisnis Islam, 2024)
This study aims to determine and analyze the influence of halal knowledge, halal awareness and religiosity on Azarine sunscreen products on Generation Z in Surabaya. This study is a quantitative research method with the approach of the spread of questionnaires with statements that refer to the indicators. Research samples were taken by purposive sampling technique. The collected data was tested using data instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that halal knowledge has an influence on the purchase interest of Azarine sunscreen products. Religiosity also has an impact on the purchase interest of Azarine sunscreen products. Meanwhile, halal awareness does not influence the purchase interest of Azarine sunscreen products. Simultaneously, halal knowledge, halal awareness, and religiosity affect purchase interest. The implications of these findings provide important insights for companies in designing more targeted marketing strategies for Generation Z, particularly in Surabaya, who consider halal knowledge and religiosity in their product purchase decisions.